3D human hands rendering by a six degrees of freedom collaborative robot and a single 2D camera - Boyack, Michael; Sices, Alexsandra; Jo, Bruce Woongyeol (IAES International Journal of Robotics and Automation (IJRA), 2023)
Human hands are essential in everyday tasks, mainly manipulating and grasping objects. Thus, accurate and precise three-dimensional (3D) models of digitally reconstructed hands are valuable to the world of ergonomics. A 3D scan-to-render system called the “3D hands model rendering using a 6-degrees of freedom (DoF) collaborative robot” is proposed to ensure that a person receives the best possible outcome for their unique anatomy. The description implies this is using a 6-DoF robot with a two-dimensional (2D) camera sensor that will encompass all forms of the production line in a timely, low-cost, precise, and accurate manner so that an individual can go to and scan their hand and have an actual 3D reconstruction print within the same facility, the same day. It is expected to generate an accurate hand model using structure from motion (SFM) system techniques to create a dense point cloud using photogrammetry. The point cloud is used to develop the tetrahedral mesh of the surface of the hand. This mesh is then refined to filter out the noise of the point cloud. The mesh can produce a precise 3D model that can tailor products to the consumer's needs. The results show the effectiveness of the 3D model of the hand.